Digital Media and the Information Age. - MOCAN, Rodica (Ekphrasis (2067-631X), 2016)
An interview with Peter Bruck, the Director of the Research Studios Austria, is presented, who discusses organizing competitions regarding digital media, development and adoption of technology, and innovation and creativity regarding digital media.